Identifikasi Faktor yang Mempengaruhi Siswa dalam Proses Pemilihan Jurusan Pendidikan Lanjutan (Studi pada Siswa Kelas XI SMA Negeri 5 Banda Aceh) - Zahra Nelissa; Sri Astuti; Martunis Martunis (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2018)
The factors in choosing a major for higher education for grade-11 students of Senior High School is the first step in preparing their future career. Before student continuing education to higher education students have to determine the right major for his/herself. The factors that influence student in choosing the major in higher education is personality factor, friend of the same age factor, and parent guidance factor. The purpose of this research is to determine the dominant factor that influence 11th grade State Senior High School 5 of Banda Aceh students in election process for major in advanced education. This research used descriptive qualitative as research approach. The total sample of this research is 138 students. The simple random sampling techniques is used in obtaining the sample of this research. The data collection in this research is using scale questionnaire. Based on the results of data analysis using the percentage of descriptive analysis, this research results indicate that there are two dominant factors affecting students in election process for major in advanced education which is personality factor with percentage of 92% and parents factor with percentage of 76%, meanwhile friend of the same age factor gives students insignificant influence in the election process for major in advanced education with percentage of 33%. The conclusion in this research is the student of 11th grade choose majors because the influence of personality factor and friend of the same age factor.